Critical Discourse Analysis on “We are the World 25 for Haiti” Song Lyrics - Herman Herman (English Education Department, 2019)
This research aims in analyzing a song entitled “We are the World 25 for Haiti”. This song was first introduced by Michael Jackson in 1985 named “We are the World 1985” when he made collaboration with other musicians for USA for Africa (United Support of Artists for Africa). The single was intended as a charity single to raise funds for famine relief efforts in Ethiopia who have suffered political instability and disaster drought in 1984-1985. Then, this song is chosen to be used for collecting funds in rehabilitating Haiti after the enormous earthquake. This paper focuses on the composer’s attitudes, the social relation among the participants, the context of the situation, and the power relation in the discourse. The lyrics are taken as the object of the research. The data were initially analyzed based on Martin and Rose (2003). The findings showed that the all types of attitude were found, they were expressing feelings, judging people’s character, and appreciating things. But one parts of judging people’s character was not found in the song lyrics. The result of the study is hoped to be beneficial for readers to have a better understanding about the Critical Discourse Analysis